Mapping cooperation: insights into Colombia's humanitarian response to migration from Venezuela - Romero, Liss Dayana; Padilla, Jose J.; Palacio, Katherine; Frydenlund, Erika (Frontiers in Human Dynamics, 2024)
Introduction Since 2015, Colombia has faced a significant humanitarian challenge, receiving 2.9 million displaced Venezuelans. This study examines organizational cooperation in the humanitarian response to this migration crisis, aiming to understand the coordination dynamics among key organizations and actors. Methods Our research combined interviews and web scraping to gather data on key actors and their relationships in the humanitarian response. We employed Social Network Analysis (SNA) to examine these relationships and the collaborative strategies among entities, focusing on how they address the migration challenges. Results The results indicate that cooperation occurred through mediated channels, where established NGOs collaborated via coordination mechanisms established by international non-governmental organizations (INGOs), often involving diaspora volunteer-based organizations and through ad-hoc coordination. We also identified that organizations specializing in specific activities often exhibited limited coordination with others operating in the same sector. Lastly, the results suggest that coordination mechanisms played a crucial role in driving activities and facilitating the diversification of responses, partly through allocating financial resources. Discussion This study contributes to the humanitarian aid and migration literature, focusing on Colombia's migration response. It employs a mixed-methods approach, including Social Network Analysis (SNA), to explore the dynamics within humanitarian networks. It highlights the role of the Venezuelan diaspora NGOs, challenging the conventional view of migrants solely as aid recipients. The research uncovers the complex roles of intermediaries and coordination mechanisms, offering new insights into constructing effective humanitarian network structures. It advocates for a collaborative and inclusive approach to managing migration situations.